2021
DOI: 10.1523/jneurosci.3200-20.2021
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Tracking of a Background Speaker Modulates the Comprehension of a Foreground Speech Signal

Abstract: Cortical tracking of a background speaker modulates the comprehension of a foreground speech signal Abbreviated title: Cortical tracking of background speech

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
16
1
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 57 publications
5
16
1
9
Order By: Relevance
“…EEG phase patterns reflect the selectivity of neural responding, with populations of neurons more likely to fire at specific phases in response to an auditory stimulus (Ng et al, 2013). Neural oscillations also entrain to stimuli at differing preferred phases depending on whether they are being attended to or being ignored (Lakatos et al, 2008;Besle et al, 2011;Horton et al, 2013;Keshavarzi et al, 2021). Power et al's data suggest that there is an optimal or preferred phase of entrainment which is necessary for accurate and efficient processing of rhythmic speech, and that this preferred phase is different in the (child) dyslexic brain when speech is the input.…”
Section: Introductionmentioning
confidence: 99%
“…EEG phase patterns reflect the selectivity of neural responding, with populations of neurons more likely to fire at specific phases in response to an auditory stimulus (Ng et al, 2013). Neural oscillations also entrain to stimuli at differing preferred phases depending on whether they are being attended to or being ignored (Lakatos et al, 2008;Besle et al, 2011;Horton et al, 2013;Keshavarzi et al, 2021). Power et al's data suggest that there is an optimal or preferred phase of entrainment which is necessary for accurate and efficient processing of rhythmic speech, and that this preferred phase is different in the (child) dyslexic brain when speech is the input.…”
Section: Introductionmentioning
confidence: 99%
“…The significant N2 difference observed may be explained by attentional selection: assuming that in a multi-stream situation, target detection must also include validating targets by taking into account the stream the candidate belongs to. Alternatively, results showing that enhancing cortical tracking of ignored speech by transcranial alternating current stimulation reduces comprehension of the target stream ( Keshavarzi et al, 2021 ) suggests that in the current study, cortical tracking of background speech for one vs. two speech streams differentially affected the segregation of the target stream. This alternative receives support from the similar pattern of N2 amplitude and confidence ratings (indexing comprehension).…”
Section: Discussionmentioning
confidence: 62%
“…Alternatively, results showing that 10.3389/fnhum.2022.952557 Scalp topography of the N2 (upper row) and P3 (bottom row) latency range for distractor syntactic violations for the three distractor streams: M2 -male speaker in the one-distractor condition, M3 -male speaker in the one-distractor condition, F3 -female speaker in the two-distractor condition. The scalp distributions were calculated from the average voltages measured from the time windows shown in enhancing cortical tracking of ignored speech by transcranial alternating current stimulation reduces comprehension of the target stream (Keshavarzi et al, 2021) suggests that in the current study, cortical tracking of background speech for one vs. two speech streams differentially affected the segregation of the target stream. This alternative receives support from the similar pattern of N2 amplitude and confidence ratings (indexing comprehension).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…tACS provides a direct method for establishing a causal relationship between external rhythms and neural oscillations. Several studies demonstrated improved acoustic and speech processing following tACS ( Jones et al, 2020 ; Keshavarzi and Reichenbach, 2020 ; Erkens et al, 2021 ; Keshavarzi et al, 2021 ; for recent reviews, see Riecke and Zoefel, 2018 ; Nooristani et al, 2021 ). Researchers have also argued for a relation between aberrant cortical tracking of speech and speech-in-noise difficulties in individuals with hearing loss ( Fuglsang et al, 2020 ; Vander Ghinst et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%